P139 CHYLE LEAK FOLLOWING RADICAL EN-BLOC OESOPHAGECTOMY WITH 2 FIELD NODAL DISSECTION: PREDISPOSING FACTORS, MANAGEMENT AND OUTCOMES. (23rd November 2019) - Milito, P; Chmelo, J; Kamarajah, S K; Madhavan, A; Wahed, S; Hayes, N; Immanuel, A; Griffin, S M; Phillips, A W
Abstract: Background: Chyle leaks may result from damage of the main thoracic duct or its tributaries during radical en-bloc sub-total oesophagectomy (STO). Treatment strategies and outcomes vary and management of this problem remains controversial. This study assessed the incidence, management and outcomes of chyle leaks in a dedicated oesophago-gastric cancer unit. Methods: A retrospective study was conducted among patients who underwent elective STO with 2-field nodal dissection for oesophageal cancer between January 1997 and March 2019. The thoracic duct was routinely ligated during surgery. The diagnosis of post-operative chyle leak was performed clinically by a consultant and it was based on high output (> 500 ml/24h) from chest and/or abdominal drains and on visual characteristics of the fluid. Results: 1320 patients underwent surgery over the time reviewed. The study group consisted of 347 (26.3%) women and 974 (73.7%) men, with a median age of 65 (IQR 13) years. Oesophageal adenocarcinoma was diagnosed in a total of 937 (70.9%) patients, while squamous cell carcinoma in 274 (20.7%) patients. 93 (7%) patients developed a chylothorax. Univariable analysis showed that lower body weight, lower BMI, female sex and histology of a squamous cell carcinoma were significant independent predictive factors for chyle leak (p<0.005). Chyle leak was associated with a higher risk of return to ITU (45.1% vs 10.1%, p<0.001) and longer hospital stays (median 21.5 vs 15 days, p=0.002). Overall in-hospital mortality was 3.7% and was significantly higher in the chyle leak group (10.75% vs 3.2%, p<0.001), although the causes of death were not directly related to it. Chyle leak was not associated with anastomotic leak, or wound and respiratory infection. Chylothorax was treated surgically in 39 (41.9%) patients and conservatively in 54 (58.1%). Between these two groups, a significant difference in terms of post-operative hospital stay and in 30-day mortality rate was seen (p< 0.002 and p=0.031, respectively). Survival rate was similar in both groups. Conclusions: Chyle Leak post oesophagectomy is associated with an increased risk of return to ITU, and longer hospital stay and increased in hospital mortality. However, surgical treatment is safe and early re-operation is recommended in order to diminish hospital stay and to decrease the 30-day mortality rate.